Successful Erlotinib Treatment for a Patient with Gefitinib-Related Hepatotoxicity and Lung Adenocarcinoma Refractory to Intermittently Administered Gefitinib - Tatsuya Nagano; Yoshikazu Kotani; Kazuyuki Kobayashi; Masahiro Katsurada; Yukihisa Hatakeyama; Suya Hori; Daisuke Tamura; Daisuke Kasai; Yasuhiro Funada; Yoshihiro Nishimura (Case Reports in Pulmonology)
A 73-year-old Japanese man was histologically diagnosed with lung adenocarcinoma harboring an exon 19 deletion in the epidermal growth factor receptor. The patient was treated with gefitinib for 6 weeks until he developed substantially elevated hepatic enzyme levels that resulted in the discontinuation of gefitinib. Gefitinib was reintroduced with an intermittent treatment schedule after the transaminase levels normalized, but the patient's enzyme levels rose again, and the cancer progressed. Gefitinib was eventually replaced with erlotinib. There was stable disease for 7 weeks without any signs of liver toxicity. Thus, erlotinib may be a beneficial and well-tolerated treatment option for patients with gefitinib-related hepatotoxicity.